2004
DOI: 10.1091/mbc.e03-10-0751
|View full text |Cite
|
Sign up to set email alerts
|

EFA6, Exchange Factor for ARF6, Regulates the Actin Cytoskeleton and Associated Tight Junction in Response to E-Cadherin Engagement

Abstract: We addressed the role of EFA6, exchange factor for ARF6, during the development of epithelial cell polarity in Madin-Darby canine kidney cells. EFA6 is located primarily at the apical pole of polarized cells, including the plasma membrane. After calcium-triggered E-cadherin-mediated cell adhesion, EFA6 is recruited to a Triton X-100 -insoluble fraction and its protein level is increased concomitantly to the accelerated formation of a functional tight junction (TJ). The expression of EFA6 results in the selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
75
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(83 citation statements)
references
References 54 publications
8
75
0
Order By: Relevance
“…In regard to the involvement of Arf6 in epithelial polarity, hyperactivation of Arf6 or overexpression of ARNO/cytohesin-2 has been reported to cause disruption of AJs and lead to loss of cell polarity (26)(27)(28). Luton et al previously reported that EFA6, another GEF for Arf6, was recruited to developing junctions upon induction of cell-cell contacts and plays a role in the formation of TJs in MDCK cells (29). However, in EpH4 cells, EFA6 was localized throughout the entire plasma membrane and did not colocalize with ZO-1 at primordial AJs and TJs.…”
Section: Discussionmentioning
confidence: 99%
“…In regard to the involvement of Arf6 in epithelial polarity, hyperactivation of Arf6 or overexpression of ARNO/cytohesin-2 has been reported to cause disruption of AJs and lead to loss of cell polarity (26)(27)(28). Luton et al previously reported that EFA6, another GEF for Arf6, was recruited to developing junctions upon induction of cell-cell contacts and plays a role in the formation of TJs in MDCK cells (29). However, in EpH4 cells, EFA6 was localized throughout the entire plasma membrane and did not colocalize with ZO-1 at primordial AJs and TJs.…”
Section: Discussionmentioning
confidence: 99%
“…EFA6 was initially implicated in regulation of transferrin receptor endocytosis, endosomal membrane recycling, and actin cytoskeleton remodeling related to membrane ruffling (42). Its role in E-cadherin recruitment and actin rearrangement for generation of tight junctions (TJs), which follows AJ assembly, and establishment of cell polarity was later described (44). EFA6 and p100 may have analogous functions in parallel pathways that regulate, respectively, TJ and AJ dynamics, including their interactions with the actin cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…The EFA6 family of proteins is composed of four members: EFA6A, EFA6B, EFA6C, and EFA6D. EFA6B and EFA6D are widely expressed in tissues, whereas EFA6A and EFA6C are predominantly expressed in brain tissues (14,15). The BRAGs include three members, among which BRAG2 shows ubiquitous expression; in contrast, BRAG1 and BRAG3 display primal expression in the brain (16).…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%
“…The former reaction is a very important ratelimiting step, as GEFs define the specificity of small GTP-binding protein activation by integrating intracellular signals. Arf GEFs are divided into five families based on overall structure and domain organization (11,12): Golgi brefeldin A (BFA)-resistance factor 1/BFA-inhibited GEF (GBF/BIG) (13), Arf nucleotide binding site opener (ARNO)/cytohesin, exchange factor for Arf6 (EFA6) (14,15), BFA-resistant Arf GEF (BRAG) (16), and F-box only protein 8 (FBX8) (17). The large number of GEFs relative to the number of Arf proteins suggests that GEF activities are controlled under extensive regulatory conditions in various types of cells.…”
mentioning
confidence: 99%